Development, Validation and Effectiveness of Instructor- made Learning Course Material (LCM) - Camuyong, Christian Sam F. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The study sought to develop and validate a learning course material and to determine its effectiveness of the instructor- made learning course material. Developmental educational research approach was utilized in attaining the research objectives. Specifically, focus group discussion protocol, adapted standardized validation instrument and instructors- made learning task was used in the development, validation and test of effectiveness of the instructor made learning course material. The study revealed that the developed learning course material is accurate, coherent, appropriate and useful, hence, considered valid based on the evaluation of subject matter experts. In addition, the learning course material is effective based on the results of the pre and posttest of the student takers.